Influence of surface treatment by laser irradiation on bacterial adhesion on surfaces of titanium implants and their alloys: Systematic review - Isadora Gazott Simões; Andréa Cândido dos Reis; Mariana Lima da Costa Valente (Elsevier, 2023)
Objective: The aim of this systematic review was to present the current knowledge on the influence of laser surface treatment on the adhesion of bacteria to titanium and its alloys. Design: This review was structured according to PRISMA guidelines for systematic reviews and meta-analyses, and registered on the Open Science Framework platform (https://doi.org/10.17605/OSF.IO/FTA3W). Article searches were performed in 4 databases: PubMed, Scopus, Embase, and Science Direct. In addition, a manual search was performed in the reference lists of the selected articles. The selection of articles was performed by two reviewers. The articles found were screened for eligibility using the previously established inclusion and exclusion criteria. The methodological quality of the studies was assessed using the Joanna Briggs Institute (JBI) Critical Assessment Checklist for Quasi-Experimental Studies (non-randomized experimental studies). Results: Most of the studies evaluated showed that surface treatment by laser irradiation can affect the adhesion of bacteria to titanium surfaces and that this is directly related to changes in surface properties such as chemical composition, morphology, roughness, and wettability, as well as the type of bacterial species involved. Conclusions: The studies considered in this systematic review have shown that surface treatment by laser irradiation is a promising technique to reduce the adhesion of bacteria on the surface of titanium implants.